(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article investigates the formation and characteristics of associative fields created by evaluative units in the Uzbek language, focusing specifically on units that express positive evaluation. It examines the role of language units in conveying the speaker’s (subject’s) attitude towards an object, a central component of communication and meaning-making. The research outlines methods for constructing and analyzing these associative fields. This includes: identifying and extracting associatively linked units from a given text; integrating these units to form the associative field; conducting associative experiments to gauge individuals’ responses to stimuli words related to positive evaluation; and, finally, constructing and analyzing the structure of the resulting associative field based on the experimental data. The study isolates and analyzes the positive evaluative units within a text, then delineates the resulting associative field for each unit. The analysis delves into the lexical, grammatical, and syntactic units that constitute and shape these associative fields, offering insights into the cognitive and linguistic mechanisms underlying positive evaluation in Uzbek. The research contributes to a deeper understanding of the interplay between language, evaluation, and the construction of meaning.